Photon-photon polarization correlations as a tool for studying parity nonconservation in heliumlike uranium - Fratini, Filippo; Trotsenko, Sergiy; Tashenov, Stanislav; Stöhlker, Thomas; Surzhykov, Andrey (Physical review. A, Atomic, molecular, and optical physics, 2011)
Due to electron-nucleus weak interaction, atomic bound states with different parities turn out to be mixed. We discuss a prospective method for measuring the mixing parameter between the nearly degenerate metastable states 1s1/22s1/2:J=0 and 1s1/22p1/2:J=0 in heliumlike uranium. Our analysis is based on the polarization properties of the photons emitted in the two-photon decays of such states.
Gesehen am 06.03.2023